1984
DOI: 10.1093/ptj/64.9.1375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trunk Stabilization on Quadriceps Femoris Muscle Torque

Abstract: The purpose of this study was to determine if differences exist in angle-specific torque, torque-velocity relationships, and power-velocity relationships of the quadriceps femoris muscle group when the trunk was and was not stabilized and the starting position was varied. We calculated isokinetic torques from seven adult men while the trunk was and was not stabilized for nine combinations of velocity of movement 0, 30, and 105 degrees/sec) and starting position (40, 60, and 100 degrees of knee flexion). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Prior to baseline testing, education sessions were held for all subjects to achieve familiarization of the testing procedures and to provide instruction in the proper muscle activation pattern required for the modified double straight leg-lowering (DSLL) test. Previous research 9 and observations during pilot testing indicated that most subjects cannot begin trunk stability testing until they have been given the opportunity to practice achieving the muscular activation pattern that is required for proper testing. Following the education session, subjects were tested on 3 measures: DSLL, vertical jump, and leg press.…”
Section: Testing Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to baseline testing, education sessions were held for all subjects to achieve familiarization of the testing procedures and to provide instruction in the proper muscle activation pattern required for the modified double straight leg-lowering (DSLL) test. Previous research 9 and observations during pilot testing indicated that most subjects cannot begin trunk stability testing until they have been given the opportunity to practice achieving the muscular activation pattern that is required for proper testing. Following the education session, subjects were tested on 3 measures: DSLL, vertical jump, and leg press.…”
Section: Testing Protocolsmentioning
confidence: 99%
“…A similar session, as originally designed by Hagins et al, 9 was modified for the purposes of this study to allow for practice of the DSLL test and to learn how to maintain trunk stability. Sessions were completed by showing a video of an investigator instructing the proper technique and having subjects practice along with the video.…”
Section: Education Sessionmentioning
confidence: 99%
“…Subjects sat in a comfortable, upright seated position on the Biodex dynamometer chair, and were secured using thigh, pelvic and torso straps in order to minimize extraneous body movements. Such extraneous body movements during isokinetic testing have been shown to result in lower peak torque generation (Hart et al 1984;Weir et al 1996). The lateral femoral epicondyle was used as the bony landmark for matching the axis of rotation of the knee joint with the axis of rotation of the dynamometer resistance adaptor.…”
Section: Isokinetic Exercisementioning
confidence: 99%
“…However, test results of the HHD can be influenced by factors such as the sensitivity and construction of the dynamometer (4), the subject's test position and stabilization (4,5) and the examiner's strength (4,(6)(7)(8)(9). A dynamometer's sensitivity may be maintained by calibration (4), while straps can be useful for subject stabilization (8,10). Methods to address this issue of examiner strength have been proposed (11)(12)(13)(14)(15)(16), but there is room for further improvement.…”
Section: Introductionmentioning
confidence: 99%